Paul D. Wolfowitz visionary intellectual, policymaker, and strategist - Solomon, Lewis D. (Praeger Security International, 2007)
A long-time State Department hand, Deputy Secretary of Defense for five years, and one of the architects of the Bush Doctrine, Wolfowitz is a crucial figure in post-Cold War foreign and security policy. This biography of Wolfowitz traces his intellectual development and bureaucratic influence at key points along the road to Baghdad and beyond